Upaya Mempertahankan Balance Cairan Dengan Memberikan Cairan Sesuai Kebutuhan Pada Klien Dhf Di Rsud Pandan Arang Boyolali - Arif Fauziah, Isna, Irdawati S. Kep., Ns, Msi. Med (2016)
Dengue fever, a contagius disease caused by the dengue virus is transmitted through the bite of Aedes Aegypthy. The disease can affect everyone, not know the age or gander. This disease is increasing every year and dominant in endemic areas. One og the other cities in Central Java province, in August, patient with dengue fever increased significantly, until Oktober seven people died because this disease. One of hospital in Boyolali is Pandan Arang Hospital has patient with incresased every year. In some patient will have problem in fluid and electrolyte disturbances. Due to the body loses overbalance fluid and electrolytes. As a result, the patient will have physical changes, such as slow skin turgor, sunken eyes, dry lips mucosa, as well as the patient will have nausea and vomiting wich causes sufferers to become anorexic, so that fluid intake is required to be less. Treathment in patients with DHF have a purpose is to describe maintain fluid balance in patients with DHF, so the problem with fluid disturbances can be resolved and there are no sign of dehydration. This method is applied in according nursing care in patients with DHF, one of independent ect to do is naintain fluid balance by providing fluid intake as needed. The effeorts have been made in comliance with the balance of fluid intake DHF patients can be met. So that, we can conclude that the handling of cases with DHF that issue is resolved, the intervention was continuid with wncouraging patients to ensure adequate intake of fluid required withweight 39kg ±1880ml/kg/24h.